DEVELOPMENT OF CO-CURRICULAR MODULES BASED ON THE LOVE CURRICULUM IN MADRASAH ALIYAH - Nurul Hikmah; Musyarapah Musyarapah (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2026)
Curriculum Love Based is curriculum initiated by the Ministry of Religion and started implemented in madrasas at the end of 2025. Implementation of KBC can done in activity Intracurricular , co-curricular and extracurricular activities . Facts on the ground show that implementation activity Co-curricular activities in various Madrasah Aliyah are still face a number of constraint Because absence existence module . Because of this that madrasah requires guidelines systematic operations so that its implementation in harmony with objective curriculum Love -based . Research objectives This is to 1) develop module co-curricular 2) feasibility and practicality research module This is Research and Development (R & D) research with the ADDIE model development model . Subject in study This is madrasah principal and staff educators at the Kapuas Regency Islamic Senior High School. Research results This show that 1) The products produced is module co-curricular use curriculum based Love with theme Humanist Madrasah: Caring Fellow , Caring Environment with allocation 16 JP time using 3 panca love and 6 Dimensions Profile graduate (DPL) . module Co-curricular activities are very much needed in madrasas for support implementation curriculum based love 2) Developed module based on expert material get score 91% or very worthy and from media experts get score 86% with very worthy category . Meanwhile For 89% practicality with very practical category.